The Effect of Service Quality, Price and Consumer Buying Interest on Customer Satisfaction at Evi Marbau Cosmetic Store - Uges Febriani (LP2M IAIN Palopo, 2026)
This study aims to determine the effect of service quality, price, and purchase intention on customer satisfaction at the Evi Marbau Cosmetics Store. This study used a quantitative approach with a survey method. The study population was customers who had visited the Evi Marbau Cosmetics Store, with an average of 120 customers per week. The research sample was determined using the Slovin formula with a 5% margin of error, resulting in 93 respondents. Data collection was conducted through a questionnaire using a Likert scale. Data analysis used multiple linear regression with partial tests (t-test), simultaneous tests (F-test), and validity and reliability tests using SPSS. The results showed that service quality, price, and purchase intention partially had a significant effect on customer satisfaction. Simultaneously, these three variables also significantly influenced customer satisfaction at the Evi Marbau Cosmetics Store. The results of the validity and reliability tests indicated that all statement items were valid and the research instrument was reliable. Therefore, improving service quality, setting appropriate prices, and increasing consumer purchase intention can improve customer satisfaction